Energy performance contracts handbook : transform your estate - Zaitsau, Viktar, ....- ([Surrey] : Ecodo, 2013)
Viktar Zaitsau is an author and a renowned expert in Energy Performance Contracts. He is a Chartered Engineer and a Member of the Chartered Institution of Building Services Engineers. Viktar has two MSc degrees: the first in Environmental Protection, Heating, Ventilation and Air Conditioning; and, the second in Building Services Engineering. He was awarded a distinction for his dissertation on Part L2a of the Building Regulations, Conservation of Fuel and Power in New Buildings other than Dwellings. Viktar has helped numerous organizations run Energy Performance Contracts, to achieve energy and maintenance savings, reduce backlog maintenance and improve building environmental conditions.
Keywords: Energie; besparing